2011
DOI: 10.1590/s2237-93632011000300007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of direct costs of anesthesia-related materials between spinal and venous anesthesia with propofol associated with local perianal block in hemorrhoidectomy

Abstract: There is no consensus on the ideal anesthesia for hemorrhoidectomy in ambulatory facilities. Spinal anesthesia and venous propofol associated with local perianal block (combined anesthesia) are frequently used, and their direct costs may be crucial for the anesthesia type selection. The objective of this study was to compare the direct costs of anesthesia-related materials in hemorrhoidectomy between these two anesthetic techniques.Retrospective and cross-section analysis, comparing the direct costs of the mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Operative time has been shown to be different according to the anesthetic technique used in terms of time saved during operation according to studies done by Kushwaha and Baghel with their colleagues comparing the use of LA versus spine and GA for open hemorrhoidectomy [ 2 , 9 ]. Despite producing interesting results presented in the literature, LA has been increasingly questioned, as to whether it brings more benefits to selected patients [ 10 ]. It was found that open hemorrhoidectomy (OH) under general anesthesia (GA) or spine anesthesia (SA) showed a high-cost implication as compared to OH done under local anesthesia in different studies published [ 2 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Operative time has been shown to be different according to the anesthetic technique used in terms of time saved during operation according to studies done by Kushwaha and Baghel with their colleagues comparing the use of LA versus spine and GA for open hemorrhoidectomy [ 2 , 9 ]. Despite producing interesting results presented in the literature, LA has been increasingly questioned, as to whether it brings more benefits to selected patients [ 10 ]. It was found that open hemorrhoidectomy (OH) under general anesthesia (GA) or spine anesthesia (SA) showed a high-cost implication as compared to OH done under local anesthesia in different studies published [ 2 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite producing interesting results presented in the literature, LA has been increasingly questioned, as to whether it brings more benefits to selected patients [ 10 ]. It was found that open hemorrhoidectomy (OH) under general anesthesia (GA) or spine anesthesia (SA) showed a high-cost implication as compared to OH done under local anesthesia in different studies published [ 2 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Economic load of health care including costs for anesthesia delivery has been increasing. Facing the global economic constraints, reduction of anesthesia cost has been a necessity [1,2]. Inhalational anesthetics accounts for 20% of the cost related to anesthetic drug costs [3,4].…”
Section: Introductionmentioning
confidence: 99%